2018
DOI: 10.1007/s40519-018-0488-z
|View full text |Cite
|
Sign up to set email alerts
|

Validity of triglyceride–glucose index as an indicator for metabolic syndrome in children and adolescents: the CASPIAN-V study

Abstract: Level V, cross-sectional descriptive study (National surveillance study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 34 publications
2
52
0
4
Order By: Relevance
“…Limited data are reported in pediatric age, in which the TyG index has been described as a useful predictor of metabolic abnormalities in Asian, Mexican American, Non-Hispanic White adolescents (15)(16)(17)(18)(19)(20)(21). Untill now there is no consensus for reference criteria in Caucasian children, besides no pediatric study has been conducted on this topic.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited data are reported in pediatric age, in which the TyG index has been described as a useful predictor of metabolic abnormalities in Asian, Mexican American, Non-Hispanic White adolescents (15)(16)(17)(18)(19)(20)(21). Untill now there is no consensus for reference criteria in Caucasian children, besides no pediatric study has been conducted on this topic.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…A study carried out with Korean adolescents aged 10-18 identified cutoff points between 8.41 and 8.66 for TyG index to predict metabolic syndrome, using different diagnostic criteria (18). Angoorani et al (19) The present study in Caucasian subjects identified an optimal cut-off of 7.98 for IR, that may be used for assessing IR and associated metabolic risk in children and teenagers with overweight and obesity, although caution is required when applied to other populations metabolically at risk. A study limitation that should be acknowledged is the lack of dietary data.…”
Section: Correlation Between Tyg and Homa-irmentioning
confidence: 99%
“…TyG index showed better performance for assessing IR than the homeostasis model assessment of IR(HOMA-IR) [7,8]. A number of studies have found a positive association between TyG index and cardiovascular risk, including systematic CAD, carotid atherosclerosis, hypertension, metabolic syndrome, arterial stiffness and coronary calcification [9][10][11][12][13][14][15]. Furthermore, recent data suggest that TyG index could provide significant prognostic information in patients with established CAD [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…У взрослых верхняя граница по данным зарубежной литературы составляет 8,8 [14]. По данным испанского исследования Gesteiro E., et al (2018), верхняя граница у новорожденных составляет 7,8 [15], а по результатам крупного иранского исследования точка отсечения у детей в возрасте от 7-18 лет -8,33 [16]. По нашим данным, индекс не выходил за рамки ориентировочно нормальных, но, тем не менее, необходимы крупномасштабные исследования на детской популяции с целью определения нормальных значений индекса в соответствии с возрастными периодами.…”
Section: обсуждение основного результата исследованияunclassified